Wawasan Gender dan Peran Produktif Perempuan Pesantren - Towaf, Siti Malikhah (Jurnal Aplikasi Manajemen, 2008)
The perspectives of people in pesantren about gender and the role of women are much more bused on their cultural and educational experience. Previous researcher show that classical textbooks as the maian sourse of education in pesantren have gender bias. Cultural heritages combine with the legacy of religious interpretations promote gender bias in pesantren. This research exlpre the perspectives of ustazd and ustadzah about gender, how is the spirit and the role of women in productive activities in pesantren and the expectations of ustadz and ustadzah about the productive role of women in the future. A qualitative research with multicases design was conducted in four pesantren in Malang Regeant. Various data were collected by documentary study, interview, observation and an open questionnaire. The result shows that eventhough the resistency toward the idea of gender equality is very strong in three pesantren, but the role of women in pesantren is very pervasive. Women area very productive in managing educational activity of female santries. They also a dependable manager and worker in economic activities such as catering, retail and home industry. Their spouses appreciate their productive activities, there is expectation among ustadz and ustadzah that women will become more professional in their productive activity in the future.